Conjugated microporous polymer / carbon nanotube composite material as well as preparation method and application thereof
Through the conjugated microporous polymer/carbon nanotube composite material, the problems of low energy density and poor fast charging stability of lithium-ion battery positive electrode materials are solved, and a high energy density and fast charging lithium-ion battery positive electrode materials are realized, suitable for future lightweight and high-performance lithium-ion batteries.
Patent Information
- Application Number
- CN202510409646.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-08-08
AI Technical Summary
The existing lithium-ion battery positive electrode materials have low energy density and poor fast charging stability, making it difficult to meet the energy storage needs of future aircraft and electric equipment.
The conjugated microporous polymer/carbon nanotube composite was used to synthesize the light and high energy density fast charging composite material through the Buchwald-Hartwig coupling reaction and the single-wall carbon nanotube template seed-induced growth strategy. The bipolar ion storage characteristics of porphyrin and anthraquinone groups were used to prepare porous materials rich in ion storage sites using the electron transport characteristics of carbon nanotubes.
It realizes a combination of high energy density and fast charging performance. The material exhibits ultra-high energy density and excellent fast charging performance in a wide operating voltage range, and is suitable for lightweight and high-performance lithium-ion batteries.
Smart Images

Figure CN120453321A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemistry, and particularly relates to a conjugated microporous polymer / carbon nanotube composite material, a preparation method thereof, and a battery constructed therefrom. Background Art
[0002] The development of near-space vehicles and electric aircraft has greatly promoted the demand for lightweight, high-performance lithium-ion batteries (LIBs) in the future. As the most critical component of lithium-ion batteries, the positive electrode plays a vital role in determining the battery's energy storage capacity. Currently, lithium-ion batteries are mainly based on inorganic materials. Due to their simple preparation and stable performance, they are the most widely studied commercial positive electrode materials. However, the mainstream inorganic positive electrode materials have limited energy density and poor fast charging stability, which makes it difficult to meet the requirements of lightweight and fast charging for future aircraft energy storage batteries. Therefore, it is crucial to develop positive electrode materials with excellent energy density and fast charging capabilities to meet the needs of energy storage devices for the next generation of near-space electric equipment.
[0003] After years of development and technological optimization, lithium-ion batteries have used materials such as ternary materials, lithium iron phosphate, and lithium cobalt oxide as lithium-ion battery positive electrodes and have been commercialized. Although the above commercial positive electrode materials can meet many usage scenarios, their low energy density and safety issues remain unresolved. In recent years, researchers have conducted numerous studies on improving the energy density of lithium-ion battery positive electrode materials, such as the development of high-voltage electrode materials, material structure adjustment, and blending modification. However, the physicochemical properties of inorganic metal oxide positive electrode materials have always limited their energy density to further breakthroughs, and there are major safety risks and poor cycle stability and fast charging performance. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a conjugated microporous polymer / carbon nanotube composite material and its preparation method and application, and in particular to a new type of lightweight, high energy density, fast-charging conjugated microporous polymer / carbon nanotube composite positive electrode material and its preparation method and application, so as to overcome the technical defects that commercial positive electrode materials on the existing market are difficult to meet the requirements of both high energy density and fast charging. The key lies in the limited energy storage sites of inorganic electrodes and the high density, and the inability to remain stable for a long time under high current density.
[0005] The invention provides a conjugated microporous polymer / carbon nanotube composite material. The conjugated microporous polymer / carbon nanotube composite material comprises a conjugated microporous polymer and carbon nanotubes, wherein the conjugated microporous polymer grows on the surface of the carbon nanotubes.
[0006] The conjugated microporous polymer comprises an alternating copolymer of porphyrin-based monomers and anthraquinone-based monomers.
[0007] In the conjugated microporous polymer / carbon nanotube composite material, the carbon nanotubes account for 10 to 60 wt % of the conjugated microporous polymer.
[0008] The present invention provides a method for preparing a conjugated microporous polymer / carbon nanotube composite material, comprising:
[0009] The porphyrin-based monomer, anthraquinone-based monomer, alkaline reagent, organic solvent, carbon nanotube, catalyst and ligand are mixed, and then reacted under anhydrous and oxygen-free conditions, purified and dried to obtain a conjugated microporous polymer / carbon nanotube composite material.
[0010] The mixing is ultrasonic mixing for 1-30 min.
[0011] Preferably, the porphyrin-based monomer includes one or more of 5,10,15,20-tetrakis(4-bromophenyl)-21H,23H-porphyrin, 5,10,15,20-tetrakis(4-bromophenyl)-porphyrin-copper(II), and 5,10,15,20-tetrakis(4-bromophenyl)-21H,23H-porphyrin. The chemical structure is as follows:
[0012]
[0013] Preferably, the anthraquinone-based monomer includes one or more of 2,6-diaminoanthraquinone, 1,5-diaminoanthraquinone, 1,4-diaminoanthraquinone, 1,2-diaminoanthraquinone, and 1,8-diaminoanthraquinone. The chemical structure is as follows:
[0014]
[0015] Preferably, the carbon nanotubes include one or more of single-arm carbon nanotubes and multi-wall carbon nanotubes; wherein the single-arm carbon nanotubes are unmodified single-arm carbon nanotubes or amino-modified single-wall carbon nanotubes.
[0016] In the conjugated microporous polymer / carbon nanotube composite material, the carbon nanotubes account for 10 to 60 wt % of the conjugated microporous polymer.
[0017] Preferably, the alkaline reagent includes one or more of sodium tert-butoxide, potassium tert-butoxide, and cesium carbonate.
[0018] Preferably, the organic solvent includes one or more of toluene, nitrotoluene, N,N-dimethylformamide, methanol, chloroform, and tetrahydrofuran.
[0019] Preferably, the catalyst comprises one or more of bis(dibenzylideneacetone)palladium(0), palladium acetate, and tris(dibenzylideneacetone)dipalladium.
[0020] Preferably, the ligand includes one or more of 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl, 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, and 1,1-bis(diphenylphosphino)ferrocene.
[0021] Preferably, the molar ratio of the porphyrin-based monomer to the anthraquinone-based monomer is ((1-2)):(2-4)).
[0022] The molar ratio of the alkaline reagent to the ligand and the catalyst is 130-260:3-6:2-4; the ratio of the porphyrin monomer to the organic solvent is 0.1 mmol:15-20 mL.
[0023] Preferably, the reaction is carried out at 60-120° C. for 1-7 days, with a stirring rate of 600-1600 rpm.
[0024] The reaction vessel used in the reaction is a pyrex tube.
[0025] The anhydrous and oxygen-free conditions are as follows: N2 is introduced into the reaction vessel and the vessel is sealed.
[0026] The purification is carried out by washing with an organic solvent or by Soxhlet extraction.
[0027] The present invention provides a battery, which comprises the conjugated microporous polymer / carbon nanotube composite material; wherein the conjugated microporous polymer / carbon nanotube composite material is used as a positive electrode material.
[0028] The electrolyte components used in the battery include lithium hexafluorophosphate LiPF6 and carbonate; the carbonate includes one or more of ethyl methyl carbonate (DMC), ethylene carbonate (EC), propyl methyl carbonate (EMC), and diethyl carbonate (DEC); the concentration of lithium hexafluorophosphate in the electrolyte is 0.5 to 2M.
[0029] Furthermore, the carbonate is DMC:EC:EMC=1:1:1 Vol%, or DEC:EC=1:1 Vol%, or DMC:EC=1:1 Vol%, or EC:EMC=3:7 Vol%, or EC:DMC=3:7 Vol%.
[0030] The battery comprises: a conjugated microporous polymer / carbon nanotube composite material, a conductive agent, and a binder are mixed to form a slurry, which is then coated on a current collector, dried and cut to form a positive electrode sheet, and then the positive electrode sheet is assembled with a lithium sheet, a separator, and an electrolyte to form a half-cell.
[0031] The mass ratio of the conjugated microporous polymer / carbon nanotube composite material, the conductive agent and the binder is (5-8): (1-4): (1-3).
[0032] Furthermore, the mass ratio of the conjugated microporous polymer / carbon nanotube composite material, the conductive agent and the binder is 5:3:2, 7:2:1 or 8:1:1.
[0033] The drying temperature is 100° C. and the drying time is 12 to 48 hours.
[0034] The amount of electrolyte added is 50-100 μL.
[0035] The present invention provides an application of the conjugated microporous polymer / carbon nanotube composite material in the field of electrochemistry, such as lithium ion batteries.
[0036] Based on the ion storage characteristics of lithium-ion battery electrode materials, the present invention designs a porous material with rich ion storage sites by utilizing the bipolar ion storage capacity of porphyrin-based and anthraquinone-based groups with both n-type and p-type active sites. Combining the rich ion storage sites and the lightweight characteristics of organic materials, the porphyrin-based conjugated microporous polymer / carbon nanotube composite positive electrode material exhibits ultra-high electrode energy density, achieving a lower electrode weight with the same energy storage capacity. While ensuring the rich active sites of the electrode, the specific surface area and pores of the porphyrin-based porous polymer are adjusted by carbon nanotubes to obtain optimized pores, so that the ion transfer rate and active site utilization rate are further increased, further improving the charging rate and electrode energy density. The conjugated microporous polymer positive electrode material can have both high energy density and excellent fast charging performance under high current density, which can meet the market demand for lightweight, high energy density and fast charging batteries.
[0037] The present invention is based on the Buchwald-Hartwig coupling reaction and the single-walled carbon nanotube template seed-induced growth strategy to synthesize a bipolar, lightweight, high-energy-density, fast-charging conjugated microporous polymer / carbon nanotube composite material combining porphyrin and anthraquinone, and use it as the positive electrode of a lithium-ion battery. The conjugated microporous polymer designed in the present invention utilizes the bipolar electrochemical energy storage properties of porphyrin and anthraquinone groups. The lithium-ion positive electrode material prepared by compounding with carbon nanotubes has the excellent electron transport properties of carbon nanotubes and the rich ion storage sites of conjugated porous materials. Thanks to the ultra-high specific surface area and highly conjugated structural system of the porous material, the utilization rate of ion storage sites and the transmission rate of electrons and ions can be greatly improved. The positive electrode material can have ultra-high energy density, excellent ultra-fast charging performance and good cycle life in a wide range of operating voltages, and has a very broad application prospect in lightweight, high-performance lithium-ion batteries in the future.
[0038] Beneficial effects
[0039] (1) The present invention utilizes the bipolar ion storage properties of porphyrin groups and anthraquinone groups to prepare a bipolar conjugated microporous polymer with porphyrin groups as the core energy storage group through the Buchwald-Hartwig cross-coupling reaction, and by compounding with carbon nanotubes to increase the specific surface area and pores of the material, a conjugated microporous polymer with bipolar active sites and rich pores is synthesized for lithium-ion battery positive electrodes. Based on the rich energy storage sites endowed by the bipolar properties and the light weight of the organic material, a high energy density of the electrode is achieved. By compounding with carbon nanotubes, the electronic conductivity of the material and the utilization rate of the active sites are improved, further improving the fast charging capacity and energy storage performance of the electrode.
[0040] (2) By utilizing the bipolar ion storage capacity of the porphyrin ring at the center of the porphyrin ring, the secondary amine bond generated by the Buchwald–Hartwig cross-coupling reaction, and the abundant aldehyde groups in the anthraquinone group, the bipolar properties of the material are further enhanced to achieve higher energy density and a wider operating voltage range. At the same time, by compounding with single-walled carbon nanotubes, the specific surface area and the number of pores of the material are increased to achieve faster ion transport and higher active site utilization.
[0041] (3) The carbon conjugated microporous polymer / carbon nanotube composite cathode material prepared by the present invention has excellent energy density and power density, and achieves high specific energy, light weight and fast charging capability. -1 The power density at the current density is as high as 22604Wkg -1 , and the charging time is only 43s.
[0042] (4) The preparation process of the present invention is simple, the equipment and machinery are mature, and large-scale production can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Schematic diagram of the reaction process for preparing the conjugated microporous polymer / carbon nanotube composite cathode material of the present invention;
[0044] Figure 2 Scanning electron microscope image of the conjugated microporous polymer / carbon nanotube composite cathode material of Example 1 at a size of 800 nm;
[0045] Figure 3 The X-ray diffraction pattern of the conjugated microporous polymer / carbon nanotube composite cathode material in Example 1;
[0046] Figure 4 The conjugated microporous polymer / carbon nanotube composite cathode material prepared in Example 1 was used as the cathode of the lithium metal half-cell at 0.3Ag -1 Long cycle performance diagram under current density;
[0047] Figure 5Energy density diagram of a lithium metal half-cell with the conjugated microporous polymer / carbon nanotube composite cathode material prepared in Example 1 as the cathode at different current densities;
[0048] Figure 6 The charge and discharge curves of the lithium metal half-cell at different current densities in Example 1;
[0049] Figure 7 The lithium metal half-cell in Example 2 is 0.3Ag -1 Long cycle performance diagram under current density;
[0050] Figure 8 The lithium metal half-cell in Example 3 is 0.3Ag -1 Long cycle performance diagram under current density
[0051] Figure 9 The lithium metal half-cell in Example 4 is 0.3Ag -1 Cycling performance diagram under current density;
[0052] Figure 10 For Example 5, the lithium metal half-cell is at 0.1Ag -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION
[0053] Below in conjunction with specific embodiment, further set forth the present invention.Should be understood that these embodiments are only used to illustrate the present invention and are not used in limiting the scope of the present invention.In addition, should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall equally within the scope limited by the appended claims of the application.
[0054] 5,10,15,20-Tetrakis(4-bromophenyl)porphyrin - Leyan Reagent - 1156425-10g
[0055] 2,6-Diaminoanthraquinone——Merrill——M38170-25G
[0056] N,N-Dimethylformamide——Shanghai trial——81007718
[0057] Toluene - Shanghai Test - 10022818
[0058] 2-Dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl——TCI——D5038-1g
[0059] Sodium tert-butoxide——Adamas——01120177
[0060] Bis(dibenzylideneacetone)palladium(0)——Sigma-Aldrich——227994
[0061] High-purity single-arm carbon nanotubes (long) - Pioneer Nano - 100216
[0062] 2,6-Dibromobenzo[1,2-b:4,5-b']dithiophene - Ron's reagent - R048168-250mg
[0063] Tetrahydrofuran——Adamas——011342849
[0064] High-purity amino-modified single-arm carbon nanotubes (long) - Pioneer Nano - 101178
[0065] Example 1
[0066] This example provides a design and preparation method for a high-energy-density, lightweight conjugated microporous polymer / carbon nanotube composite organic lithium-ion battery cathode, comprising the following steps:
[0067] (1) Dissolve 372.0 mg of 5,10,15,20-tetrakis(4-bromophenyl)-21H,23H-porphyrin, 190.4 mg of 2,6-diaminoanthraquinone, and 80 mg of single-arm carbon nanotubes in a mixed solvent of N,N-dimethylformamide / toluene (20 / 40 mL), place in a 100 mL pyrex tube, and sonicate for 30 min. Add 22.9 mg of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 200 mg of sodium tert-butoxide, and 18.4 mg of bis(dibenzylideneacetone)palladium(0), and purge N2 into the reaction vessel, then seal it. Place in a 120°C oil bath, stir, and heat for 48 h. After cooling to room temperature, Soxhlet extraction was performed with chloroform, N,N-dimethylformamide, and methanol, respectively, and then vacuum dried at 100°C for 12 hours to obtain a carbon nanotube-composite porphyrin-based porous organic polymer cathode material.
[0068] (2) The porphyrin-based conjugated microporous polymer / carbon nanotube composite material was ground and mixed with a conductive agent and a binder in a mass ratio of 5:3:2 to prepare a slurry. The slurry was then coated on an aluminum foil current collector and dried to prepare a positive electrode sheet with a diameter of 12 mm. The positive electrode sheet was assembled with a 16 mm diameter PP separator, a 12 mm diameter lithium metal sheet, and 70 μL of 1 M LiPF6 in DMC:EC:EMC = 1:1:1 Vol% commercial electrolyte to form a button half-cell.
[0069] Test the microscopic morphology of carbon nanotube composite porphyrin-based porous organic polymer cathode materials, such as Figure 2Scanning electron microscope images show that the material stacking becomes looser through compounding with unmodified single-arm carbon nanotubes, resulting in a larger specific surface area and higher active site utilization, providing better conditions for increasing the material's energy density and mass transfer rate.
[0070] The prepared conjugated microporous polymer was used as the positive electrode material for lithium-ion batteries and assembled into a lithium metal half-cell. The results were tested at 0.3 A g -1 Cycling performance under current density. Figure 4 As shown, the conjugated microporous polymer cathode is 0.3Ag in the lithium metal half-cell system. -1 The current density was 620Wh kg -1 The energy density is 325.53 mAh g -1 discharge capacity.
[0071] At the same time, the power density and energy density of the lithium metal half-cell system at various current densities were tested. Figure 5 As shown in Figure 2, the porphyrin-based conjugated microporous polymer / carbon nanotube composite cathode exhibits a high conductivity at 0.3 A g -1 The current density was 734Whkg. -1 High energy density and high energy density at 10Ag -1 270Wh kg at ultra-high current density -1 High energy density and 22604Wkg -1 Ultra-high power density. And, Figure 6 The charge and discharge curves of the material at various current densities show its ultra-wide operating voltage range and excellent rate performance, and it shows great application prospects in the fields of high performance and fast charging.
[0072] Example 2
[0073] This example provides a design and preparation method for a high-energy-density, lightweight porphyrin-based conjugated microporous polymer / carbon nanotube composite organic lithium-ion battery cathode, specifically referring to Example 1, except that the N,N-dimethylformamide / toluene mixed solvent in step (1) is replaced with tetrahydrofuran and the reaction temperature is changed to 70°C, and the electrolyte in step (2) is changed to 1MLiPF6 in EC:EMC=3:7Vol%.
[0074] The assembly of the lithium metal half-cell was the same as in Example 1, except that the prepared conjugated microporous polymer / carbon nanotube composite material was used as the positive electrode material for the lithium ion battery to assemble into a lithium metal half-cell. -1 Cycling performance under current density. Figure 7 As shown, the conjugated microporous polymer cathode exhibits a high conductivity at 0.3 A g in a lithium metal half-cell system. -1The current density was 856Wh kg -1 The energy density is 453.45 mAh g -1 discharge capacity.
[0075] Example 3
[0076] This example provides a design and preparation method for a high-energy-density, lightweight porphyrin-based conjugated microporous polymer / carbon nanotube composite organic lithium-ion battery cathode. The method specifically refers to Example 1, except that the N,N-dimethylformamide / toluene mixed solvent in step (1) is replaced with tetrahydrofuran and the reaction temperature is changed to 70°C. Furthermore, the single-arm carbon nanotubes in step (1) are replaced with amino-modified single-arm carbon nanotubes, and the addition amount is changed to 10 wt%.
[0077] The assembly of the lithium metal half-cell was the same as in Example 1, except that the prepared conjugated microporous polymer / carbon nanotube composite material was used as the positive electrode material for the lithium ion battery to assemble into a lithium metal half-cell. -1 Cycling performance under current density. Figure 8 As shown, the conjugated microporous polymer cathode exhibits a high conductivity at 0.3 A g in a lithium metal half-cell system. -1 The current density was 794Wh kg -1 The energy density is 418.83 mAh g -1 discharge capacity.
[0078] Example 4
[0079] This example provides a design and preparation method for a high-energy-density, lightweight porphyrin-based conjugated microporous polymer organic lithium-ion battery cathode, which is specifically referred to Example 1, except that the single-arm carbon nanotubes in step (1) are removed.
[0080] The assembly of lithium metal half-cell is the same as that in Example 1, except that the prepared conjugated microporous polymer is used as the positive electrode material of lithium ion battery to assemble into lithium metal half-cell, and its cycling performance at a current density of 0.3Ag-1 is tested. Figure 9 As shown, the conjugated microporous polymer cathode exhibited a 400Whkg-1 current density at 0.3Ag-1 in a lithium metal half-cell system. -1 The energy density is 184.48 mAh g -1 discharge capacity.
[0081] Example 5
[0082] This example provides a design and preparation method for a high-energy-density, lightweight porphyrin-based conjugated microporous polymer organic lithium-ion battery positive electrode, specifically referring to Example 1, except that while removing the single-arm carbon nanotubes in step (1), the 2,6-diaminoanthraquinone is replaced with the same amount of 2,6-dibromobenzo[1,2-b:4,5-b']dithiophene.
[0083] The assembly of lithium metal half-cell is the same as that of Example 1, except that the prepared conjugated microporous polymer is used as the positive electrode material of lithium ion battery to assemble into lithium metal half-cell. -1 Cycling performance under current density. Figure 10 As shown, the conjugated microporous polymer cathode is 0.1Ag in the lithium metal half-cell system. -1 The current density was 257Wh kg -1 The energy density is 120.86 mAh g -1 discharge capacity.
Claims
1. A conjugated microporous polymer / carbon nanotube composite material, characterized in that: The conjugated microporous polymer / carbon nanotube composite material comprises a conjugated microporous polymer and carbon nanotubes, wherein the conjugated microporous polymer grows on the surface of the carbon nanotubes.
2. A method for preparing a conjugated microporous polymer / carbon nanotube composite material, comprising: The porphyrin-based monomer, anthraquinone-based monomer, alkaline reagent, organic solvent, carbon nanotube, catalyst and ligand are mixed, and then reacted under anhydrous and oxygen-free conditions, purified and dried to obtain a conjugated microporous polymer / carbon nanotube composite material.
3. The preparation method according to claim 1, characterized in that The porphyrin-based monomer includes one or more of 5,10,15,20-tetrakis(4-bromobenzene)-21H, 23H-porphyrin, 5,10,15,20-tetrakis(4-bromobenzene)-porphyrin-copper(II), and 5,10,15,20-tetrakis(4-bromo)-21H; the anthraquinone-based monomer includes one or more of 2,6-diaminoanthraquinone, 1,5-diaminoanthraquinone, 1,4-diaminoanthraquinone, 1,2-diaminoanthraquinone, and 1,8-diaminoanthraquinone.
4. The preparation method according to claim 1, characterized in that The carbon nanotubes include one or more of single-arm carbon nanotubes and multi-wall carbon nanotubes; wherein the single-arm carbon nanotubes are unmodified single-arm carbon nanotubes or amino-modified single-wall carbon nanotubes.
5. The preparation method according to claim 1, characterized in that: The alkaline reagent includes one or more of sodium tert-butoxide, potassium tert-butoxide, and cesium carbonate; the organic solvent includes one or more of toluene, nitrotoluene, N,N-dimethylformamide, methanol, chloroform, and tetrahydrofuran; The catalyst comprises one or more of bis(dibenzylideneacetone)palladium(0), palladium acetate, and tris(dibenzylideneacetone)dipalladium; The ligand includes one or more of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, and 1,1-bis(diphenylphosphino)ferrocene.
6. The preparation method according to claim 1, characterized in that: The molar ratio of the porphyrin-based monomer and the anthraquinone-based monomer is (1-2): (2-4); the molar ratio of the alkaline reagent to the ligand and the catalyst is 130-260: 3-6: 2-4; and the ratio of the porphyrin-based monomer to the organic solvent is 0.1 mmol: 15-20 mL.
7. The preparation method according to claim 1, characterized in that: The reaction is carried out at 60-120° C. for 1-7 days; In the conjugated microporous polymer / carbon nanotube composite material, the carbon nanotubes account for 10 to 60 wt % of the conjugated microporous polymer.
8. A battery, characterized in that: The battery comprises the conjugated microporous polymer / carbon nanotube composite material according to claim 1; The conjugated microporous polymer / carbon nanotube composite material is used as the positive electrode material.
9. The battery according to claim 8, characterized in that: The electrolyte components used in the battery include lithium hexafluorophosphate LiPF6 and carbonate; the carbonate includes one or more of ethyl methyl carbonate, ethylene carbonate, methyl propyl carbonate, and diethyl carbonate; the concentration of lithium hexafluorophosphate in the electrolyte is 0.5 to 2M.
10. Use of the conjugated microporous polymer / carbon nanotube composite material according to claim 1 in the field of electrochemistry.